Aggregate supply and demand determinants of economic growth in West Sumatra, Indonesia: A dynamic panel approach - Satrianto, Alpon; Amar, Syamsul; Fitra, Halkadri; Ikhsan, Akmil; Gusti, Mia Ayu (Asian Journal of Economic Modelling, 2026)
This study investigates the determinants of economic growth in West Sumatra Province over the period 2011–2023, focusing on both supply- and demand-side factors. A dynamic panel regression model is employed using the Generalized Method of Moments approach, which is particularly suitable for addressing potential endogeneity issues and capturing temporal dynamics in panel data analysis. The explanatory variables include aggregate supply-side factors, namely lagged economic growth, investment, labor, technology, and the Human Development Index (HDI), as well as aggregate demand-side factors, consisting of household consumption, government expenditure, and net exports. The estimation results reveal that, on the supply side, previous economic growth, investment, technology, and HDI exert a positive and statistically significant impact on regional economic growth, while labor does not show a significant effect. On the demand side, household consumption and government expenditure are found to have significant positive influences, whereas net exports are not statistically significant, reflecting the limited contribution of export activities to the regional economy. These findings highlight the dual importance of supply-side improvements and demand-side reinforcement in sustaining economic growth.